2007
DOI: 10.1093/pcp/pcm108
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Chloroplast Enzymes in Galdieria sulphuraria in View of Eukaryotic Evolution

Abstract: Redox modulation is a general mechanism for enzyme regulation, particularly for the post-translational regulation of the Calvin cycle in chloroplasts of green plants. Although red algae and photosynthetic protists that harbor plastids of red algal origin contribute greatly to global carbon fixation, relatively little is known about post-translational regulation of chloroplast enzymes in this important group of photosynthetic eukaryotes. To address this question, we used biochemistry, phylogenetics and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 61 publications
1
67
0
Order By: Relevance
“…The lack of response of the pea PRK/GAPDH/CP12 complex to NADPH is not strictly consistent with all of the previous studies on this complex possibly because of differences in the techniques used to visualize the complex (15,16,25,27). Alternatively, this may reflect the differences in metabolic regulation between cyanobacteria, algae, and higher plants (25,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 56%
“…The lack of response of the pea PRK/GAPDH/CP12 complex to NADPH is not strictly consistent with all of the previous studies on this complex possibly because of differences in the techniques used to visualize the complex (15,16,25,27). Alternatively, this may reflect the differences in metabolic regulation between cyanobacteria, algae, and higher plants (25,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 56%
“…sulphuraria must have evolved alternative mechanisms to distribute TP into various pools (i.e. floridean starch, floridoside, and fatty acid and amino acid synthesis), such as less stringent redox control of Calvin cycle, OPPP, and glycolysis (Oesterhelt et al, 2007). Plastidial phosphate translocators thus represent crucial components of primary carbon portioning in higher plants and red algae that have evolved to the specific requirements of each lineage through modulation of substrate specificities and kinetic constants.…”
Section: Resultsmentioning
confidence: 99%
“…In photosynthetic tissues, plastidic FBPase is inactivated at night and thus hexose-Ps cannot be generated from TPs (and vice versa). In contrast, red algal starch biosynthesis is cytosolic and plastidic FBPase from G. sulphuraria is not subject to a strict redox regulation (Reichert et al, 2003;Oesterhelt et al, 2007). Importing TPs via the GsTPT could thus sustain the production of hexose-P for carbon and NADPH supply in the rhodoplast during the night or prolonged heterotrophic growth conditions, thus bypassing the requirement for a plastidic hexose-P translocator (Fig.…”
Section: G Sulphuraria Does Not Possess a Plastidic Hexose-p Importermentioning
confidence: 99%
“…CP12 is a small (approximately 80-amino acid) protein present in most photosynthetic organisms, including cyanobacteria, diatoms, red and green algae, and higher plants (Pohlmeyer et al, 1996;Wedel and Soll, 1998;Oesterhelt et al, 2007;Erales et al, 2008b;Groben et al, 2010). In eukaryotic organisms, CP12 is located in the chloroplast, where the only function thus far identified is in the regulation of the Calvin cycle in response to changes in light availability by reversibly binding glyceraldehyde-3-P dehydrogenase (GAPDH) and, subsequently, phosphoribulokinase (PRK; Wedel et al, 1997;Graciet et al, 2003aGraciet et al, , 2003bMarri et al, 2005aMarri et al, , 2008Erales et al, 2008a;Howard et al, 2008;Carmo-Silva et al, 2011).…”
mentioning
confidence: 99%
“…In vitro analysis of Arabidopsis CP12 mutants has shown that both pairs of redox-regulated Cys residues are required for ternary complex formation: an N-terminal pair for PRK binding and a C-terminal pair for GAPDH binding (Wedel et al, 1997). The red alga Galdieria sulphuraria CP12 does not have an N-terminal Cys pair, and although the GAPDH-PRK-CP12 complex forms, PRK is not completely inactivated (Oesterhelt et al, 2007). In the cyanobacterium Synechococcus elongatus sp.…”
mentioning
confidence: 99%